Asuhan keperawatan pada ibu postpartum menggunakan terapi jus labu siam untuk menurunkan tekanan darah - Veni Andriyani; Rilyani Rilyani; Aryanti Wardiyah (THE JOURNAL OF Mother and Child Health Concerns, 2023)
Background: Hypertension is a non-communicable disease and the main cause of premature death worldwide. The World Health Organization (WHO) currently estimates that the prevalence of hypertension worldwide is 22% of the total world population. Approximately 10.4 million deaths are attributed to hypertension as the main factor of cardiovascular disease. Meanwhile, the cause of maternal death other than bleeding and infection is postpartum hypertension. Hypertension is responsible for approximately 165% of deaths annually worldwide and is a major contributor to morbidity and mortality associated with cardiovascular disease. Approximately 10% of maternal deaths are caused by hypertensive disorders of pregnancy that occur in the postpartum period. Purpose: providing nursing care by administering chayote juice to lower blood pressure in postpartum mothers with hypertension in Way Terusan Village, Central Lampung in 2024. Method: This research uses quantitative methods with descriptive research types with a case study approach to nursing care, which includes assessment, nursing diagnosis, planning, implementation and evaluation. Results: Nursing care carried out on 2 patients who received the same therapy showed that there was an effect of giving chayote juice on reducing blood pressure in postpartum mothers, namely at the beginning before administration, Ny.T blood pressure was 160/100 mmHg to 120/80 mmHg, while for Ny.S at the beginning before administering blood pressure from 160/90 mmHg to 110/80 mmHg. Conclusion: Nursing care provided to Ny. T and Ny. S using chayote juice therapy to lower blood pressure so that blood pressure decreases and can be controlled. Keywords: Chayote Juice; Hypertension; Postpartum. Pendahuluan: Hipertensi merupakan penyakit tidak menular dan penyebab utama kematian dini di seluruh dunia. Organisasi Kesehatan Dunia (WHO) saat ini memperkirakan prevalensi hipertensi di seluruh dunia adalah 22% dari total populasi dunia. Sekitar 10,4 juta kematian dikatikan dengan hipertensi sebagai faktor utama dari penyakit kardiovaskular. Sedangkan untuk penyebab kematian ibu selain perdarahan dan infeksi adalah hipertensi postpartum. Hipertensi bertanggung jawab sekitar 16,5% kematian tiap tahunnya diseluruh dunia dan merupakan penyumbang utama morbiditas dan mortalitas yang berhubungan dengan penyakit kardiovaskuler. Sekitar 10% kematian ibu disebabkan gangguan hipertensi kehamilan yang terjadi pada periode postpartum. Tujuan: Melakukan asuhan keperawatan dengan pemberian Jus Labu Siam Untuk Menurunkan Tekanan Darah pada Ibu Postpartum dengan hipertensi di Desa Way Terusan Lampung Tengah Tahun 2024. Metode: Penelitian ini menggunakan metode kuantitatif dengan jenis penelitian deskriptif dengan pendekatan studi kasus asuhan keperawatan, yang meliputi pengkajian, diagnosa keperawatan, perencanaan, pelaksanaan, dan evaluasi. Hasil: asuhan keperawatan yang dilakukan terhadap 2 pasien yang mendapatkan terapi yang sama didapatkan hasil adanya pengaruh pemberian jus labu siam terhadap penurunan tekanan darah pada ibu postpartum, yaitu diawal sebelum pemberian tekanan darah Ny.T 160/100 mmHg menjadi 120/80 mmHg sedangkan untuk Ny.S diawal sebelum pemberian tekanan darah 160/90 mmHg menjadi 110/80 mmHg. Simpulan: asuhan keperawatan yang dilakukan pada Ny.T dan Ny.S dengan menggunakan terapi jus labu siam untuk menurunkan tekanan darah sehingga tekanan darah menurun dan dapat terkontrol.